Pengaruh Persepsi Kemudahan Dan Persepsi Kemanfaatan Terhadap Minat Konsumen Menggunakan Kartu Mandiri E-Money Bank Mandiri - Shita, Rae (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2020)
This study aims to determine the effect of perceived convenience on consumer interest in using E-Money cards. To determine the effect of perceived usefulness on consumer interest using E-Money cards. To determine the effect of perceived convenience and perceived usefulness on consumer interest using Bank Mandiri E-Money cards Muara Teweh Branch. In this study, multiple regression analysis acts as a statistical technique used to test whether or not the perceived effect of perceived convenience and perceived usefulness on consumer interest shows that there is a positive influence on perceived convenience and perceived usefulness simultaneously on consumer interest in using cards. Mandiri e-money. From the research results, it is known that the determination analysis used to determine the percentage of the contribution of the influence of the independent variables together on the dependent variable is obtained by an Adjusted R Square of 0.839 or (83.9%). This shows that the percentage of the contribution of the influence of the independent variable, namely the perception of convenience and the perception of usefulness, together has a positive effect on consumer interest in using Mandiri e-money cards by 83.9%. Henceforth, it is suggested that the Company should make it easier to refill balances and Mandiri e-card transactions. -money so that consumers work faster in using the Mandiri e-money card. The company added more machines that support e-money Mandiri cards to increase productivity.